COVID-19 and Tuberculosis: A perspective of Bangladesh - Rahman, Mohammed Atiqur; Ahmed, Shamim; Paul, Shipan Chandra; Ferdousi, Kazi Rahila (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Tuberculosis is our old enemy while COVID-19 (Coronavirus disease 2019) is a novel one. Both diseases have many similarities in terms of target organ affected, transmission, clinical presentations. COVID-19 is a fast-track novel pandemic while tuberculosis is a slow-moving pandemic. As control measures, countries all over the globe have enforced lockdown to halt the spread of the SARS-CoV-2 virus, but this stringent method has a negative impact on access to the health care delivery system. It seems that there is a dropping of new case findings, but modeling projection by WHO estimates that the total number of tuberculosis cases will rise by 2025. Bangladesh is a high Tuberculosis burden country in the south Asia region. Worldwide COVID-19 has a negative impact on tuberculosis diagnosis and management strategy. Bangladesh has impending threat to rise in tuberculosis case in future because of lockdown process, densely populated nation, poverty, reallocation of tuberculosis diagnostic facility and trained staff to diagnose COVID-19 and collapse of DOTS (directly observed treatment, short-course) program of NTP (national tuberculosis control program), rampant use of immunosuppressant’s including steroid, biologics. Prompt tuberculosis case detection, digital supervised drug delivery, avoidance of injudicious use of steroids, biologics to treat COVID-19, and testing for both COVID-19 and tuberculosis should be simultaneously undertaken to tackle this overwhelming situation. Eradication of psycho-social stigma about these two diseases is essential for preventing a perfect storm. BSMMU J 2022; 15(1): 54-56